Gods, Graves and Scholars : the story of archeology - Ceram, C. W. (Knopf Alfred, 1952)
Pompeii -- Troy -- Mycene -- Crete -- The empire of Egypt -- The kingdoms of Assyria, Babylonia, Sumeria -- The empires of the Toltecs, the Aztecs, and the Mayas